Effect of Dietary Crude Protein Levels on Egg Production, Hatchability and Post-Hatch Offspring Performance of Indigenous Chickens - Kingori, A.M.; Tuitoek, J.K.; Muiruri, H.K.; Wachira, A.M. (International Journal of Poultry Science, 2010)
Indigenous chickens in Kenya are estimated to be 21.5 million and are found in all the ecological zones in the country. They are 75% of the poultry population and produce 46 and 58% of the egg and meat, respectively. These levels of production are comparatively low compared to their numbers. The low productivity of indigenous chickens in Kenya and other parts of the world is partly attributed to poor management practices, in particular the lack of proper healthcare, poor nutrition and housing. This study was designed to determine the effects of dietary protein levels on egg production, hatchability and post-hatch offspring feed intake, feed efficiency and growth rate of indigenous chickens. Seventy two hens averaging 46 weeks in age, were offered four diets formulated from similar ingredients but differing in protein levels: 100, 120, 140 and 170 g CP/kg DM. Diets were randomly allocated to hens such that each diet had nine replicates each consisting of two hens. The hens were housed in battery cages and diets offered ad-libitum. Laying percentage, egg weight and feed intake were measured over an 8-week period. There was an increase (p0.05) at 120 and 140 g CP/kg DM. The laying percentage of hens offered 170 g CP/kg DM was lower (p0.05) on offspring feed intake (51-56 g), live weight gain (6.5 -8.5 g / day) and feed conversion efficiency (0.13-0.15). It is, therefore, concluded that the dietary crude protein requirement for laying indigenous hens is about 120 g CP/kg and maternal dietary protein level has no effect on hatchability and post-hatch offspring feed intake, feed efficiency and growth rate. The findings will help in the formulation of indigenous chicken layer diet with the appropriate protein content.